Shadows beyond theatre. Talk with Ronaldo Robles e Silvia Godoy – Quase Cinema Co. (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This is an edited and corrected version of the interview given on November 1, 2024, by Ronaldo Robles and Silvia Godoy, founders of the Cia Quase Cinema shadow theater, and producers of the FIS – International Shadow Theater Festival, to Mario Piragibe. The discussion addresses the reasons for the creation of the mentioned Shadow Theater Festival, which completed 11 years since its foundation in 2024, and the impacts, both projected and observed, of both the FIS and the artistic work of Cia Quase Cinema. The conversation also addresses the close relationships between the principles that govern the festival and the poetic processes of the company, and the vision of its founders regarding offering a responsible legacy, not only to the field of art.